STUDY OF GOETHITE TO HEMATITE TRANSFORMATION BY MECHANOCHEMICAL FOLLOWED BY MAGNETIC SEPARATION FOR LATERITIC IRON ORE BENEFICIATION - BAKRI - NIM: 22115025 , SURIYANTO
The existence of steel industry is very strategic for the prosperity of a country. National steel consumption in 2025 is estimated to reach 19.12 million tons while domestic industry will only be able to produce 10 million tons (Ministry of Commerce Indonesia, 2017). This condition is caused by the inability of the domestic iron ore companies to prepare the raw materials for steelmaking. The lateritic iron ore resources of Indonesia is estimated at 3,921.8 million tons, whilst its reserves is approximated at 736.9 million tons (Geological Resource Center, 2016). Fe element content of 39.8 - 55.2% in the deposit is not yet possible to be used as raw material for steel making. FeOOH content and some impurities in the lateritic iron ore require pretreatment prior to the concentration process to improve the Fe grade. In this research, pretreatment of phase transformation in the lateritic iron ore by mechanochemical process followed by magnetic separation were carried out. The mechanochemical phase transformation aims to convert the goethite phase into hematite and or magnetic so that the Fe content can increase as well as decreasing the particle size into nanometer size. Hematite nanoparticles are useful in technology, health and the environment aspects. The mechanochemical grinding experiments were conducted by using planetary ball mill with variation of time at 5, 20, 35 and 50 hours; mill volume percentage of 20%, 30%, 40% and 50%; and ball type of steel and ceramic. The optimum result of product obtained in mechanochemical experiments was then used as feed for magnetic separation using dry magnetic separator. It was shown that the lateritic iron ore from Sebuku Island, South Kalimantan used in this experiment was categorized as ferromagnetic ore. The iron ore was dominated by goethite (FeOOH) and maghemite (γFe2O3) with Fe content of 42.68%. The transformation of the goethite into hematite and maghemite into magnetite were perfectly occurred after 50 hours of grinding process, at 50 percent mill volume and with mill ball of steel type. The Fe content of the product reached 53.03% with the particle size distribution (D90) of 54.30 nm. The mechanochemical process also gave an effect on the magnitude of the lateritic iron ore magnetism i.e. the magnetic field intensity value of 6.23 to 9.55 emu/gram. From the experiment of magnetic separation, it was shown that the Fe content was slightly increased to be 53.33% and with a recovery of 88.44%.